IMPLEMENTASI PERFORMANCE ASSESSMENT DALAM EVALUASI HASIL BELAJAR MAHASISWA PADA MATA KULIAH TEORI PRAKTEK BOLA VOLI - Nasuka, - (Jurnal Penelitian Pendidikan, 2010)
Volleyball subject is both theory and practice subject. In accordance with the standards of competence and basic competence to be achieved, this course, beside providing the theory of playing volleyball game, also consist of playing the game in the field. Based on the characteristics of the course it is necessary to assess both theory and practice aspect. Performance assessment is an alternative assessment that covers all aspects of student ability. Research was carried out by implementing evaluation tools to asses learning outcomes through early field trials and the second field trials. In addition, studentsÃ¢â¬Å¸ perceptions are collected through the questionnaire and teacherÃ¢â¬Å¸s perception through interview. Learning outcomes in both early and later field trials showed good results. There are 98% of students agreed with the application of the evaluation system. Lecturer stated that itÃ¢â¬Å¸s a practical system. Keywords: Performance assessment; evaluation tools; volleyball